Current Insights into the Role of the Growth Hormone-Insulin-Like Growth Factor System in Short Children Born Small for Gestational Age - Renes, Judith S. (Horm Res Paediatr, 2019)
BACKGROUND: The reason for the insufficient catch-up growth seen in 10% of children born small for gestational age (SGA) is poorly understood. Disturbances in the growth hormone (GH) − insulin-like growth factor (IGF) axis might underlie this failure to show sufficient catch-up growth. CONCLUSION: This review summarizes insights gained in the molecular and (epi) genetic mechanisms of the GH-IGF axis in short children born SGA. The most notable anomalies of the IGF system are the lowered IGF-I levels in both cord blood and the placenta, and the increased expression of IGF-binding proteins (IGFBP)-1 and IGFBP-2, which inhibit IGF-I, in the placenta of SGA neonates. These observations suggest a decreased bioactivity of IGF-I in utero. IGF-I levels remain reduced in SGA children with short stature, as well as IGFBP-3 and acid-labile subunit levels. Proteolysis of IGFBP-3 appears to be increased.